ECT beyond unipolar major depression: systematic review and meta‐analysis of electroconvulsive therapy in bipolar depression. (16th December 2018) - Bahji, A.; Hawken, E. R.; Sepehry, A. A.; Cabrera, C. A.; Vazquez, G.
Abstract : Objective: In this systematic review and meta‐analysis, the response, remission, and speed of response in adults with major depressive disorder (MDD) and bipolar disorder in depressive episode (BDD) receiving an acute course of electroconvulsive therapy (ECT) were quantitatively analyzed. Methods: Using the Preferred Reporting Items for Systematic Reviews and Meta‐analysis guidelines, 1660 citations were identified through five electronic databases. Nineteen articles met final inclusion criteria for meta‐analysis. Results: The pooled response and remission rates with ECT in MDD were 74.2% ( n = 1246/1680) and 52.3% ( n = 850/1626), respectively. In BDD, they were 77.1% ( n = 437/567) and 52.3% ( n = 275/377), respectively. Although response rates to ECT were statistically higher in BDD (OR = 0.73, 95% CI: 0.56–0.95, P = 0.02), remission rates were similar (OR = 0.91, 95% CI: 0.65–1.26, P = 0.56). Individuals with BDD vs. MDD required fewer number of ECT sessions to achieve response (SMD = −0.23, 95% CI: −0.44 to −0.023, P = 0.03). There were no significant moderator effects identified. Conclusion: Response rates and speed of response are higher in individuals with BDD; however, remission rates are equivalent. These findings support increased utilization of ECT in individuals with treatment‐refractory BDD.